2008
DOI: 10.1007/s00414-008-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the skeletal age determination method of Tanner and Whitehouse for forensic age diagnostics

Abstract: The present paper analyses the applicability of the clinically prevalent skeletal age determination method of Tanner and Whitehouse for forensic age estimation in living individuals. For this purpose, the hand X-rays from 48 boys and 44 girls aged 12-16 years were evaluated retrospectively. The minima and maxima, the mean values with their standard deviations as well as the medians with upper and lower quartiles, are presented for the skeletal ages 12-16 years estimated by the TW2 and TW3 methods. In the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 30 publications
1
39
1
6
Order By: Relevance
“…These two parameters evaluated in this study showed indicators of biological maturation with relative dependence on chronological age, confirmed by the peculiar characteristic presented by a significant part of the sample with anon time profile, with approximation of the chronological age statistical data with G&P results for bone age. The parameterized statistics of this study contradict the one found by Schmidt et al [16] which indicates the application of the TW3 method, arguing that several protocols of radiology analysis were not adequate due to the risk of overestimating values.…”
Section: Discussioncontrasting
confidence: 91%
“…These two parameters evaluated in this study showed indicators of biological maturation with relative dependence on chronological age, confirmed by the peculiar characteristic presented by a significant part of the sample with anon time profile, with approximation of the chronological age statistical data with G&P results for bone age. The parameterized statistics of this study contradict the one found by Schmidt et al [16] which indicates the application of the TW3 method, arguing that several protocols of radiology analysis were not adequate due to the risk of overestimating values.…”
Section: Discussioncontrasting
confidence: 91%
“…For the remaining age groups of 17 to 22, the mean value for stage H did not change in comparison to all age groups (15)(16)(17)(18)(19)(20)(21)(22). The mean value for stage D however increased considerably by almost 2 years from 16.4 to 18.2 (see Table 3, stage D).…”
Section: Significance Of Mean Valuesmentioning
confidence: 81%
“…Forensic age estimation in living persons is a current area of research in the field of forensic science [2,10,20,21]. At the Institute for Legal Medicine at the University of Zurich (IRMZ), age estimations in living adolescents and young adults in the context of criminal investigations and asylum procedures have been carried out since 1999.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Katılımcılar kimlik yaşı gruplandırması yapılarak incelendiğinde; hukuki, sosyal ve ekonomik alanlarda önemli olan yaşlarda (12,15,18,21) yoğunlaştığı; en sık 63 (%45) kişi ile 15-18 yaş grubunda başvuru yapıldığı, bu oranın Büken ve ark. ile Baransel Isır ve ark.nın çalışmalarıyla uyumlu olduğu gözlendi.…”
Section: Discussionunclassified
“…Buna rağmen bazen diş yöntemleriyle sağlanan sonuçların, iskelet gelişimine göre değerlendirilen yöntemlerden daha güvenilir olduğuna literatürde işaret edilmektedir. [17][18][19] Diş, yaş tayininde değerli bir malzemedir. Çocuk-luk döneminde diş gelişim aşamalarını gözlemlemek yaş tayininde yüksek derecede doğru sonuçlar vermekte, fakat bireyin diş gelişimini tamamlamasıyla birlikte doğru sonuç oranı azalmaktadır.…”
unclassified